2020
DOI: 10.1037/trm0000218
|View full text |Cite
|
Sign up to set email alerts
|

Compassion fatigue in animal care workers.

Abstract: Similar to human services professionals working with traumatized individuals, animal care workers also report experiences of secondary trauma. For animal care workers, the literature examines secondary trauma effects through concepts such as compassion fatigue, burnout, moral stress, and perpetration-induced traumatic stress. Research suggests that veterinarians and veterinary technicians/assistants and staff suffer from compassion fatigue and burnout. The current article reports results from a survey of 2,878… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(70 citation statements)
references
References 53 publications
0
69
0
1
Order By: Relevance
“…First of all, burnout was higher in individuals working more hours per week. As this is a known risk factor for burnout this is to be expected (27). Second, burnout was higher in individuals working at a university in comparison to a contract research organization.…”
Section: Demographic and Work Factorsmentioning
confidence: 81%
See 1 more Smart Citation
“…First of all, burnout was higher in individuals working more hours per week. As this is a known risk factor for burnout this is to be expected (27). Second, burnout was higher in individuals working at a university in comparison to a contract research organization.…”
Section: Demographic and Work Factorsmentioning
confidence: 81%
“…Euthanasia Surprisingly, personnel who euthanized animals more frequently (e.g., daily vs. monthly) did not consistently report higher levels of compassion fatigue; there was no association between these two factors. Previously, more frequent euthanasia was identified as a risk factor for veterinary, animal control, and related professionals (27). However, euthanasia in the laboratory may be characteristically different from euthanasia in an animal shelter or hospital.…”
Section: Animal Stressmentioning
confidence: 99%
“…In addition, a loss of autonomy and decreased control over the work environment have been found to be common factors leading to burnout (15). Factors found to contribute to burnout in veterinarians include excessive workload and work hours, on-call duties, limited resources, workplace conflicts, and the unique challenges that come with euthanasia (7,(16)(17)(18)(19)(20). Additional stressors for veterinary professionals include unrealistic expectations from pet owners, situations where they need to balance the affordability of treatment with the provision of high quality care, and low income paired with high debt load (12, [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, studies have explored the role of enabling resources that may enhance worker engagement, meaningful work and well-being while reducing feelings of burnout and compassion fatigue (25)(26)(27). Work factors that appear to mitigate burnout, for physicians and veterinarians alike, include schedule control, opportunities for professional development and the use of skills and knowledge, the ability to develop and use their skills, respect from colleagues, and a feeling of satisfaction with one's position/job (4,16,18). Cake et al (25) proposed that animal care workers' opportunities for self-actualization may result from applying their specialized skills and knowledge to meeting the challenges of their work and that self-actualizing work may enhance their engagement, feelings of accomplishment and personal growth as well contribute to a sense of being involved in meaningful work.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study suggested that annual incidence of Post-Traumatic Stress Disorder (PTSD) in animal shelter employees is five times higher than the national average [ 3 ]. Along with PTSD, animal shelter employees often suffer from secondary traumatic stress (STS) [ 4 ]. STS is the reaction occurring in caregivers resulting from prolonged exposure to the stress associated with helping or wanting to help traumatized or suffering victims and differs from PTSD only in actual exposure to trauma [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%